Associations of Communication, Work-Related Distractions, and Workload with Patient Safety Incidents among Nurses - Della Fatma Sari; Indasah Indasah; Agustin (Innovative Approaches in Health Science Journal, 2026)
Background: Patient safety incidents remain a problem in the delivery of primary health care because they can reduce the quality of care and endanger patients. Various factors suspected of contributing to patient safety incidents at community health centers include communication, work interruptions, and the workload of health care workers. The purpose of this study was to analyze the determinants of patient safety practices in relation to patient safety incidents at community health centers in Kediri Regency. Methods: The study design used in this research was a quantitative, analytical, cross-sectional study. The population consisted of all nurses at community health centers in Kediri Regency, totaling 321 respondents. The study sample comprised 178 respondents. Proportional cluster sampling was used. The independent variables were communication, work-related interruptions, and patient safety incidents, while the dependent variable was patient safety incidents. Results: The results of the study showed that communication had a significant effect on patient safety incidents (p=0.000; r=0.507), work-related interruptions had a significant effect (p=0.000; r=0.529), and workload also had a significant effect (p=0.000; r=0.553). Multiple linear regression analysis showed that communication was the most dominant factor influencing patient safety incidents (β=2.536; p=0.012), followed by work-related interruptions (β=2.308; p=0.022) and workload (β=2.067; p=0.040). Collectively, communication, work-related interruptions, and workload had a significant effect on patient safety incidents (p=0.000) with an Adjusted R² value of 0.276, indicating that these three variables account for 27.6% of the variation in patient safety incidents, while 72.4% is influenced by other factors outside the research model. Discussion: Strengthening effective communication, controlling work-related interruptions, and managing workload appropriately are necessary to improve the patient safety culture and the quality of health services at community health centers.